INTERNALISASI MANHAJ MELALUI KEPEMIMPINAN KEPALA PENDIDIKAN DALAM MENANAMKAN PENDIDIKAN KARAKTER - Carnawi, Carnawi (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2023)
This research was conducted at Al-Bahjah Islamic Boarding School, Sentang Village, Sumber District, Cirebon Regency. The purpose of this study is to find out 1) How the internalization of manhaj through the Head of Education at Al-Bahjah Islamic Boarding School in shaping the character of school residents, 2) How the implications of internalizing manhaj in instilling character in the educational environment of Al-Bahjah Islamic Boarding School, 3) What are the supporting and inhibiting factors in internalizing manhaj through the Head of Education at Pesantren Al-Bahjah. This research uses qualitative methods with a descriptive approach. Data collection techniques carried out are by means of interviews, field observations, questionnaires, and review of relevant books. Data analysis and data interpretation techniques are carried out by data reduction, datadisplay, and data verification. The results of this study are efforts or steps to internalize manhaj, namely by improving all aspects of tarbiyah at the Al-Bahjah Islamic boarding school. The implications of internalizing manhaj in the context of instilling character education are felt by the foundation community, although there are several supporting and inhibiting factors for the internalization of the manhaj.